Antifungal activity of phenolic compounds identified in flowers from the North Eastern Portugal against Candida species - Alves, Carlos (2014)
Aim: To evaluate the antifungal effect of gallic acid, catechin, luteolin and quercetin, phenolic compounds identified from flowers of the North Eastern Portugal, against Candida planktonic and biofilm cells. Materials and Methods: The minimal inhibitory concentrations (MIC) were determined in Candida planktonic cells and the effect of phenolic compounds on Candida biofilms was assessed through quantification by colony forming units (CFUs). Results: MIC values demonstrated that gallic acid presented the highest effect against the all Candida species. Catechin showed a similar effect against C. albicans ATCC 90028cells. Additionally, gallic acid and quercetin had demonstrated only a minimum effect against Candida species biofilms. Conclusions: Gallic acid affected the growth of the different planktonic Candida species in all concentrations used, still catechin showed a similar effect against C. albicans ATCC 90028and C. glabrata ATCC 2001cells.Additionally, only gallic acid and quercetin demonstrated a slight effect against all Candida species biofilms.